Detection of biofilm-related genes and antibiotic resistance in Acinetobacter baumannii isolated from clinical specimens - SHNA OTHMAN KAKA SAADULLA; SIRWAN MUHSIN MUHAMMED (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Saadulla SOK, Muhammed SM. 2023. Detection of biofilm-related genes and antibiotic resistance in Acinetobacter baumannii isolated from clinical specimens. Biodiversitas 24: 1809-1816. A total of 53 Acinetobacter baumannii clinical isolates were collected from patients treated at Shar Hospital in Sulaimani city to determine antibiotic susceptibility patterns and their association between biofilm formation and the distribution of biofilm-related genes. Identification of suspected A. baumannii was carried out by conventional and molecular approaches, including 16S rRNA and blaoxa-51 gene amplification. In addition, disk diffusion and microtiter plate methods determined antibiotic susceptibility and biofilm-forming capability, respectively. Out of 53 A. baumannii clinical isolates 42 (79.24%), were Multidrug-Resistant (MDR), of which 3 (5.66%) were resistant to colistin. Overall, 33 (62.26%) of the clinical isolates were strong biofilm producers, 6 (11.32%) were moderate or weak biofilm producers, and 8 (15.09%) were non-biofilm-forming isolates. The frequency of biofilm-related genes ompA, bap, csuE, blaPER-1, and cpaA among A. baumannii strains was 92.45%, 79.24%, 73.58%, 9.43%, and 7.54%, respectively. The high frequency of multi-drug resistant strains, and their ability to form biofilms, is a potential threat to effective therapy and may increase morbidity and mortality in infected patients. Colistin appeared to be the most effective antibiotic for treating MDR A. baumannii infections.